Systematic review of the training process of minimally invasive surgery in neonates and infants - Zahradníková, Petra; Babala, Jozef; Lindák, Martin; Pechanová, Rebeka; Hnilicová, Silvia; Molnár, Marián; Nedomová, Barbora; Poš, Lucie; Dotlačil, Vojtěch; Kučerová, Barbora (Pediatric surgery international, 2025)
PURPOSE: Minimally invasive surgery (MIS) in neonates and infants presents technical challenges and is still unfamiliar to many paediatrics surgeons. This study aims to identify currently available simulators for neonatal/infant MIS training, to assess their validity, level of evidence, and related recommendations. METHODS: The review followed PRISMA guidelines and was registered in PROSPERO (CRD420250581050). Electronic search limited to English articles was performed through PubMed/MEDLINE, SCOPUS, Web of Science and Cochrane Database from January 2010 to June 2024. RESULTS: Out of 1084 identified records, 72 studies met the inclusion criteria and were analysed across general, gastrointestinal, thoracic, and urological MIS specialties. Recent efforts have led to the development of 3D-printed, animal-based, and hybrid models several of which showed high fidelity, skill differentiation, and educational value. Despite promising results, no universal MIS training model exists for neonate/infant patients, highlighting the need for structured, proficiency-based curricula. Overall, studies demonstrated moderate levels of evidence and recommendation, supporting integration of cost-effective simulation into paediatrics MIS training CONCLUSION: This systematic review highlights the need for validated, standardized simulation models and proficiency-based curricula to optimize neonate and infant MIS training and guide future research toward improving model fidelity, accessibility, and long-term educational outcomes.
Keywords: Thoracoscopic surgery; Simulation-based training; Infant, Newborn; Pediatrics; miniinvazivní chirurgické výkony; kojenec; tréninková simulace; Minimally invasive surgery; lidé; Simulation models; Simulation Training; (MIS) in neonates and infants; Minimally Invasive Surgical Procedures; Humans; Infant; pediatrie; novorozenec; Clinical Competence; klinické kompetence; Laparoscopic surgery